RELIABILITY ANALYSIS OF THE PRELIMINARY DESIGN OF METROCAPSULE PROPULSION SYSTEM WITH FAILURE MODES EFFECTS AND CRITICALITY ANALYSIS METHOD - Hadi, Fachrie
Traffic congestion often occurs in big cities, one example is the city of Bandung. One of the efforts made by the Bandung City Government is by creating public transportation called metro capsule. Metro capsule have several systems that function to control the metro capsule. The systems on the metro capsule coordinate with one another, so that the metrocapsule can operate automatically without using a driver and only requires an officer to deal with emergencies. The metro capsule propulsion system is the only system that functions to move the metrocapsule. Therefore, high reliability of the metrocapsule propulsion system is required. To fulfill the regulation and purpose of the metro capsule, it is necessary to analyze the reliability of the metrocapsule, especially the metrocapsule propulsion system. The method used in this undergraduate research is the failure modes effects and critically analysis (FMECA) method. FMECA analysis aims to reduce the probability of failure by knowing the modes, effects, and causes of failure of the metro capsule propulsion system. In addition, the critical components of the metro capsule propulsion system can also be identified from the results of FMECA analysis. Recommendations will be given to the critical components of the metro capsule propulsion system hoping that they can be taken into consideration in the development of the metrocapsule propulsion system design.